A structural equation modeling approach to investigate HIV testing willingness for men who have sex with men in China - Han Jiang; Wei He; Haiying Pan; Xiaoni Zhong (AIDS Research and Therapy, 2023)
Abstract Background A substantial risk of contracting Human immunodeficiency virus (HIV) exists among men who have sex with men (MSM), and HIV infection rates have been rising. This study aimed to analyze the factors influencing the Chinese MSM population’s intention to test for HIV. Methods Nonprobability sampling techniques were employed in June 2022 to recruit MSM in Chongqing and Sichuan, China. The data were analyzed using structural equation modeling (SEM), which is based on the knowledge-attitude-behavior (KAB) theory. Results Among 1687 participants, 964 (57.1%) of the MSM were willing to have an HIV test. The results of the structural equation modeling (SEM) showed that knowledge, attitude, and behavior all influenced the testing intention, with attitude having the greatest impact (total effect of 0.22). Conclusion HIV testing needs to be increased among MSM as they exhibit a moderate willingness to test. Improving education on HIV knowledge and risk behavior might enhance the willingness of MSM to test for HIV in China.